1992
DOI: 10.1007/bf02540942
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid concentration in processed cheese

Abstract: 425The conjugated linoleic acid (CLA) concentration of a variety of processed cheese products ranged between 3.2 to 8.9 mg/g fat. Processing cheddar cheese at temperaturcs of 80°C and 90°C under atmospheric conditions increased (p < 0.05) CLA content, while processing under nitrogen (70°C, 85°C) had no effect. Increasing concentrations of whey protein concentrate (WPC) and its low molecular weight (LMW) fraction from 0 to 6% increased CLA formation. Six percent WPC and LMW fraction pre~ duced a 35% and 19% inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
3
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 17 publications
5
95
3
3
Order By: Relevance
“…These values agree with those reported by Pestana et al [15] and Regula et al [21] who reported that pasteurization, depending on its type, causes different changes in the free fatty acid profiles of ewes' milk, which in general has a higher content of CLA as compared to cows' milk [22]. However, Shantha et al [17] and Garcia-Lopez et al [23] reported that the application of heat enhanced the formation of linoleic acid radicals and increased CLA content during the production of natural and processed cheeses. The average content of CLA detected during the present work, in raw, thermized and pasteurized were not significantly different.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These values agree with those reported by Pestana et al [15] and Regula et al [21] who reported that pasteurization, depending on its type, causes different changes in the free fatty acid profiles of ewes' milk, which in general has a higher content of CLA as compared to cows' milk [22]. However, Shantha et al [17] and Garcia-Lopez et al [23] reported that the application of heat enhanced the formation of linoleic acid radicals and increased CLA content during the production of natural and processed cheeses. The average content of CLA detected during the present work, in raw, thermized and pasteurized were not significantly different.…”
Section: Resultssupporting
confidence: 90%
“…The contents of CLA detected in raw-milk cheeses (10.8 ± 4.2 mg/g lipid) and in pasteurized-milk cheeses (9.6 ± 0.5 mg/lipid), were not significantly different (p > 0.05). However, Shantha et al [17] reported an enhancement of CLA formation at elevated temperatures during preparation of processed cheeses. The difference with our data may results from the fact in the present work the heating processing was applied to milk and at a much lower temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the influence of the type of cheesemaking technology was relatively low since for each one of the latter FA, it only contributed to 0.4% and 5.3% of the compositional variability in cheese fat, respectively. Previous works devoted to the study of the effect of the cheese-making process on the FA composition of cheese were mainly focused on conjugated linoleic acid (CLA) [29,32,34,42,48,73]. As in the present work, Gnädig et al [32] and Jiang et al [42] found no effect of the manufacturing conditions on the CLA content of a French Emmental cheese and of two common types of Swedish hard cheeses, respectively.…”
Section: Fatty Acidssupporting
confidence: 48%
“…Processed cheese is manufactured by blending shredded natural cheeses with emulsifying agents and then heating the blend under partial vacuum while agitating, until a homogeneous mass is formed. Ha et al [26] and Garcia-Lopez et al [21] reported increased levels of CLA in processed cheeses as compared with natural cheeses, and Shanta et al [74,75] showed that an increase in processing temperature and the addition of whey protein concentrate could increase CLA concentration during the preparation of processed cheese. The studies of van Nieuwenhove et al [80] and Luna et al [49] support that heating at a high temperature does not raise CLA levels in milk fat.…”
Section: Heating and Processed Cheesementioning
confidence: 99%